The structural causes of political crisis in Turkey - (:unkn) unknown (SETA, 2014)
The December 17th process was started allegedly by a political move by the Gülen movement, which, until recently, had been seen as a religious organization. As the government and the parliament - institutions of democratic representation - countered this move through the use of their constitutional powers, the debate has turned into a totalistic and ontological struggle. However, very few people argue that the problems are actually not independent of the constitutional system of the Turkish Republic, but rather unavoidable consequences of the existing system. If we consider the political steps and strategies pursued by the Gülen movement, we see that we are faced with the most familiar game in Turkish political history, namely the shaping of politics through the use of state institutions.